Abstract relational thinking ability of high school students through the rigorous mathematical thinking (RMT) approach to algebra topics - Nuraisyah, Raisya Novita; Pratiwi, Weni Dwi; Aisyah, Nyimas; Kurniadi, Elika; Araiku, Jeri; Astuti, Puji (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Algebra teaching at RMT is designed to involve students in consciously and deliberately practicing the formation of conceptual elements from mathematical functions. This research is a qualitative descriptive study which aims to see the emergence of indicators on levels think relational abstract with use approach RMT on the topic of algebra, material on Systems of Linear Equations with Three Variables. The research subjects in this study were 26 students of SMA in Palembang class Implementation procedures study consists from three stages that is stage preparation, stage implementation, and data analysis stage. The research was conducted in three meetings, the first meeting and second done in a way offline using the RMT approach, as well as meeting third he gave question test abstract relational abilities online through the zoom meetings application. The results of research obtained at SMA in Palembang class well, based on students being able to reach indicators of the level of abstract relational thinking.